On Students’ Well-being in the Indian Context A Review - Gairola, Vineet; Mishra, Prabhat Kumar (JOURNAL OF INDIAN EDUCATION, 2020)
The aim of this review paper is to understand and theorise different researches in the field of student well-being in the Indian context. The field of education and schooling are the doorways to realising one’s potential to the fullest. However, behavioural and psychological problems in students continue to increase. Educationists, counselors, researchers, and teachers need a feasible approach to create a facilitating environment for the students engaged in teaching-learning process. This paper will focus on how mental health and students’ well-being are connected. Helpful interventions related to students’ well-being will be discussed. Researches on how gender, school climate, self-esteem, meaning making process, emotional intelligence, and academic achievement relate to psychological well-being will be explored.